2017
DOI: 10.18800/boletindearqueologiapucp.201702.011
|View full text |Cite
|
Sign up to set email alerts
|

Una mirada hacia el futuro: nuevas direcciones en la arqueología de los Andes nororientales

Abstract: IntroducciónSi bien en la introducción revisamos el desarrollo de los estudios regionales y las rutas por las cuales llegamos al momento en que nos encontramos, en este capítulo contextualizamos los artículos anteriores entre las tendencias actuales y consideramos las direcciones futuras que la arqueología regional promete seguir. Discutimos las cuestiones más urgentes que quedan por resolver, las bases de datos que hoy en día faltan para llegar a estas metas y concluimos con una mirada al rumbo que podría seg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…hen and how much humans altered humid Andean montane forests is debated. It was long argued that these systems were virtually uninhabitable [1][2][3] , but recent archaeological [4][5][6] and palaeoecological 7,8 data show long-term occupation of some settings but not others 9 . Recently, it has been suggested that the Andean forests of today may have been treeless fields at the time of the European conquest 8,10 .…”
mentioning
confidence: 99%
“…hen and how much humans altered humid Andean montane forests is debated. It was long argued that these systems were virtually uninhabitable [1][2][3] , but recent archaeological [4][5][6] and palaeoecological 7,8 data show long-term occupation of some settings but not others 9 . Recently, it has been suggested that the Andean forests of today may have been treeless fields at the time of the European conquest 8,10 .…”
mentioning
confidence: 99%
“…Paleoecological evidence from lake sediment samples indicates human occupation in and adjacent to Chachapoyas prior to 4000 BCE and maize cultivation by 2200 BCE [17], while more direct radiocarbon evidence from the pre-Hispanic site of Lamud Urco attests to human occupation by 1500 BCE [18]. Archaeologists have recovered numerous 14 C dates pointing to widespread occupation after 1 CE [19,20], but the few systematic multiregional surveys may show sampling bias.…”
Section: The Land and The Climatementioning
confidence: 99%
“…Despite a lack of sociopolitical unification, local societies are referred to as "Chachapoya" (the 's' is dropped when referring to social groups, in order to de-Hispanicize the term). In any case, "Chachapoyas" is an eponym conveniently used to characterize societies deemed similar for the purposes of reference and/or imperial administration [8][9][10]. Unfortunately, we have little reliable ethnographic or ethnohistorical information to aid understanding of these groups, who experienced a rapid and nearly complete demographic collapse after their conquest [11,12], caused by European diseases, conscription by Inkas and Spaniards to fight wars, internecine violence, forced labor to bear cargo for El Dorado expeditions, and abuse by Spaniards who expected a continuing stream of tribute income despite shrinking numbers of Indigenous tributaries.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence that the Utcubamba valley was deforested and cultivated on terraced slopes has been gathered and analyzed by Plekhov [20] and colleagues, but the extent of such landscape transformation remains unknown. A longitudinal analysis based upon ground-level fieldwork with subsurface sampling of walled and unwalled terraces allowed an estimate of terrace construction and use beginning by AD 1, which coincides with a proliferation of Early Intermediate Period occupations throughout the region [9,21]. Records of climate and environmental change analyzed by climatologists and paleoecologists provide indications of substantial regional climate change over time.…”
mentioning
confidence: 99%